The Role of Spiritual Well-Being on the Psychological Resilience of Chronic Disease Patiens - Mad Zaini; Luh Titi Handayani; Nailatul Aulia; Farah Nur Amalia Putri (GLOBAL HEALTH SCIENCE GROUP, 2026)
Resilience and spiritual well-being are important aspects of life. Objective: This study aims to analyze the relationship between psychological resilience and spiritual well-being in individuals with chronic illnesses. The researcher used a cross-sectional approach to analyze this study. The sample consisted of 106 respondents living in Jember Regency. The researcher selected the sample using a purposive sampling technique. Data for this study were collected using a structured questionnaire administered to eligible respondents. The questionnaire was distributed electronically, and participants provided responses based on their experiences and perceptions related to the variables under investigation. Data were analyzed using the Pearson Correlation test. The results of the univariate test showed that the average score of psychological resilience was 64.70, and the average score of spiritual well-being was 22.35. The results of the bivariate test proved that there was a relationship between resilience and spiritual well-being in respondents (p-value = 0.000). The conclusion of this study is that there is a relationship between resilience and spiritual well-being in individuals with chronic illnesses in Jember Regency.